The Payment System : Design, Management, and Supervision - Summers, Bruce (International Monetary Fund, 1994)
This book, edited by Bruce J. Summers, makes a practical contribution to increased understanding of payment system design and management and of the relationship between the payment system and monetary policy. the authors of the 12 papers included in the book are central banking experts from around the world who draw on their experiences in providing technical assistance to the cental banks of the countries of the former U.S.S.R.